IMPLEMENTASI DIVERSI OLEH JAKSA PENUNTUT UMUM DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK (Studi Kasus Di Kejaksaan Negeri Karanganyar Tahun 2020) - Awan Ashari; Herwin Sulistyowati (Scholar Center, 2021)
The purpose of this study was to find the procedures for implementing diversion against child crime by the public prosecutor and to find the factors that hindered the public prosecutor during the implementation of diversion. This study uses the empirical legal method. The results of this study are 9 out of 17 cases were successfully diverted during January-December 2020 by the Public Prosecutor at the Karanganyar District Attorney. In diverting the case, the Public Prosecutor at the Karanganyar District Attorney's Office experienced 3 (three) obstacles, among others, (1) there is no consent or agreement between the victim and the perpetrator for diversion; (2) the short and limited period for seeking diversion; and (3) the crime is grossly high to divert.